TAXATION, ACCOUNTING AND BUSINESS ASPECTS OF CORPORATE RESTRUCTURING IN THE FORM OF QUASI REORGANISATION - Fitriana Fitriana; Alexandre de Sousa Guterres; Eko Nugroho Aditiya Utama Putra; Vip Paramarta; Kosasih (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
Quasi reorganisation is a corporate restructuring process that involves comprehensive adjustments in taxation, accounting and business strategy aspects to address financial issues and improve operational performance. The process requires strategic financial management and adjustment of accounting practices to reflect a more accurate economic position post-restructuring. In the context of taxation, quasi reorganisation makes use of tax provisions to optimise tax burden and strengthen cash flow, while in accounting, the process involves the reassessment of assets and liabilities and the presentation of transparent financial statements. From a business perspective, restructuring demands revision of strategies and operational models to improve competitiveness and market position. The main objectives of quasi reorganisation are to strengthen the financial and operational structure of the company, ensure long-term sustainability, and increase value for stakeholders. This study analyses how the effective integration of taxation, accounting, and business strategy in quasi reorganisation can be the key to successful corporate restructuring.